Cechy somatyczne oraz zdolności motoryczne 10-letnich uczniów ze Szkoły Podstawowej nr 20 w Bydgoszczy = Features and somatic motor skills 10-year students of primary School No 20 in Bydgoszcz - Trzonkowski, Rafał; Napierała, Marek; Małgorzata Pezala, Małgorzata Pezala; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Trzonkowski Rafał, Napierała Marek, Pezala Małgorzata, Zukow Walery. Cechy somatyczne oraz zdolności motoryczne 10-letnich uczniów ze Szkoły Podstawowej nr 20 w Bydgoszczy = Features and somatic motor skills 10-year students of primary School No 20 in Bydgoszcz. Journal of Education, Health and Sport. 2016;6(3):181-199. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.48311 http://ojs.ukw.edu.pl/index.php/johs/article/view/3441 https://pbn.nauka.gov.pl/works/722371 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.03.2016. Revised 20.03.2016. Accepted: 23.03.2016. CECHY SOMATYCZNE ORAZ ZDOLNOŚCI MOTORYCZNE 10-LETNICH UCZNIÓW ZE SZKOŁY PODSTAWOWEJ NR 20 W BYDGOSZCZY Features and somatic motor skills 10-year students of primary School No 20 in Bydgoszcz Rafał Trzonkowski, Marek Napierała, Małgorzata Pezala, Walery Zukow Uniwersytet Kazimierza Wielkiego w Bydgoszczy Słowa kluczowe: cechy somatyczne, zdolności motoryczne, uczniowie 10-letni Key words: somatic features, motor skills, students 10-year-old Streszczenie Celem badań było ustalenie poziomu cech somatycznych i zdolności motorycznych dzieci dziesięcioletnich ze Szkoły Podstawowej nr 20 w Bydgoszczy. Przeprowadzono badania (39 uczniów i 49 uczennic z czterech klas czwartych) budowy somatycznej oraz zdolności motorycznych z wykorzystaniem pięciu prób Międzynarodowego Testu Sprawności Fizycznej: 1. Dziewczęta przewyższają wysokością ciała rówieśniczki z badań ogólnopolskich i są od nich lżejsze. Z kolei chłopcy z badań własnych są niżsi od dzieci spoza regionu, jednak charakteryzują się większą masą ciała. Poziom dymorfizmu wysokości ciała wśród obu badanych grup jest zbliżony i nie wykazuje istotności. 2. Wskaźnik BMI jest analogiczny ze średnią krajową dzieci w badanym wieku. 3. Najliczniejszą grupę stanowią leptosomatycy. 4. Zdolnością motoryczną, która dominuje ponad rówieśnikami z badań ogólnopolskich jest gibkość. 5. Badane zdolności motoryczne uczniów ze Szkoły Podstawowej nr 20 są na zbliżonym poziomie do rówieśników z badań ogólnopolskich (ze wskazaniem jednak na dzieci spoza regionu). 6. Poziom dymorfizmu badanych cech somatycznych i zdolności motorycznych przypisać można na korzyść dziewcząt. Abstract The aim of the study was to determine the level of somatic and motor skills of children ten years of Primary School No.20 inBydgoszcz. Conducted the study (39 students and 49 students from four classes fourths) of the construction of somatic and motor skills with the use of five trials of the International Physical Fitness Test: 1. Girls surpass the height of the body with counterparts nationwide research and are lighter on them. In turn, the boys from own research are lower than children from other regions, however, have greater weight. The level of dimorphism of body height among both groups is similar and shows no relevance. 2. BMI is similar to the national average of children in the studied age. 3. The largest group are leptosomatyc. 4. The ability motive that dominates more than peers from nationwide research is flexibility. 5. examined motor skills of students from the Primary School No. 20 are at a similar level to their peers nationwide study (indicating, however, children from outside the region). 6. The level of dimorphism studied somatic features and motor skills can be assigned in favor of girls.